COVID-19 associated multiple cranial neuropathies - M. Yu. Maksimova; Ya. O. Grusha; E. I. Fettser (Неврология, нейропсихиатрия, психосоматика, 2022)
The polymorphism of the clinical manifestations of coronavirus infection often creates great diagnostic difficulties for the practitioners, especially in patients with a predominance of neurological symptoms. Of the latter, cranial neuropathies take a particular place, as they may be either one of the first symptoms or appear during the disease progression. Impairment of smell and taste is considered an early manifestation of SARS-CoV2 infection. Similar to the involvement of the olfactory bulb, multiple cranial nerves involvement (for example, VII, VI, and III) has been described. Patients with COVID-19 associated multiple cranial neuropathies are more likely to experience partial recovery of impaired function. We present and discuss a rare case of COVID-19 associated multiple cranial neuropathies with a sequential involvement of the olfactory (I), right visual (II), frontal branch of the trigeminal (V), facial (VII), and hypoglossal (XII) nerves. Data on clinical manifestations and diagnostic criteria for this form of pathology are presented.